A multicriteria framework for selecting information communication technology alternatives for climate change adaptation. Issue 1 (31st December 2022) - John A., Adebisi; Damilola E., Babatunde; Olubayo M., Babatunde
Abstract: The numerous consequences of climate change worldwide have precipitated research efforts to realise sustainable development goal 13 (SDG 13). SDG 13 has recommended mitigation and adaptation strategies to combat climate change, and many of these can be achieved using emerging technologies. Research has shown the efficacies of information communication technologies (ICTs) in mitigating and adapting to climate change. However, the selection and ranking of ICT tools for mitigating and adapting to climate change is a multicriteria problem. This paper presents a multicriteria framework that identifies and ranks the various ICT tools that can ensure climate change mitigation and adaptation. A fuzzy-technique for order of preference by similarity to ideal solution method is used as the basis of this model and tested using information obtained from an expert. The results show that the most ideal ICT alternative is social media with a closeness coefficient of 0.62, while the least preferred alternative is the intelligent system with a closeness coefficient of 0.17. The proposed model can be used in the planning of climate change adaptation strategies in developing countries where finances are usually a major constraint in implementing climate change action.